Determinants of Police and Community Cooperation in Policing: A Case of Imenti North Sub-County, Meru County (Kenya) - Mugambi, Patrick Mwongera (Advances in Social Sciences Research Journal, 2018)
ABSTRACT This study sought to examine the determinants of police and community cooperation in policing Imenti North Sub – County within Meru County Jurisdiction. The focus was on five locations of Imenti North Sub – County namely; Municipality, Ntima East, Ntima West, Nyaki East and Nyaki West. The study used interview schedule method to collect data from 183 respondents who included household heads, Chiefs, Community Policing Committee members and police officers. Data was analyzed with the aid of Statistical Package for Social Sciences (SPSS) version 20. Lack of trust and confidence in the police were found to be the key hindrances to community – police co-operation in Imenti North Sub-County. This study recommends that police agencies should build partnerships with the citizens in order to increase their ability to maintain law and order and therefore solve crimes.